Peningkatan Kapasitas Produksi dan Penjualan Produk Ikan BUMG Peumakmue Syuhada Kota Lhokseumawe Melalui Teknologi Pengeringan serta Digital Marketing - Mizan Maulana; Hasdyna, Novia; Mustaqim, Mustaqim (Lembaga Dongan Dosen, 2024)
Village-Owned Enterprises Peumakmu Syuhada in improving the economy of group members by processing freshwater and marine fish as the main business of the partner group. Smoked fish production is still carried out on a small scale and also has not used modern smoking technology. The purpose of this service is to overcome the problems that partners often face in this economic aspect, namely sales that have not been maximized, sales by entrusting or selling directly are currently still being carried out by partners without taking advantage of the digitalization that is currently developing. Conventional smoking equipment has many weaknesses which of course often hinder the production of smoked fish This smoked fish household industry is still operating using conventional smoking equipment. The results of the service include the training of the community in producing smoked fish and active digital marketing in MSMEs fostered by Village-Owned Enterprises. marketing activities include branding that uses various website-based media. Examples are blogs, websites, adwords, and various kinds of social media networks developed in MSMEs. Conventional smoking equipment is only made of wood and shelves made of bamboo and is still open so that the efficiency of smoke to smoke / cook fish is less than optimal. This PKM provides partners with cooling technology (frezer) to place raw fish ingredients so that they are not easily rotten or dirty. This technology can increase production from 150kg/day to 300kg/day or 2 times the previous one with a 100% increase and can cut production time from 5 hours to 3 hours. production time from 5 hours to 3 hours.